PENGARUH PANJANG SERAT TERTANAM TERHADAP KEKUATAN GESER INTERFACIAL KOMPOSIT SERAT BATANG MELINJO-MATRIKS RESIN EPOXY - Chandrabakty, Sri (Jurnal MEKANIKAL, 2011)
This research is aimed to understand the effect of length-embedded fibres to interfacial shear strength on epoxy resin composite reinforced â€œmelinjoâ€ stem fibres. Pull-out testing was performed with variation of length-embedded fibres including 1 mm, 3mm, and 5mm. Prior to pull-out testing, fibres were treated with boiling with water media and 5% NaOH media. The results showed that fibres with surface treatment using boiling of 5%NaoH have higher interfacial fibre shear strength, but fibres without surface treatment have lower interfacial fibre shear strength. For length - embedded fibre, the highestÂ  interfacial fibre shear strength were obtained on the length-embedded fibre respectively from 1 mm, then 3 mm and 5mm.